Case studies of quality primary education in Bangladesh - Nath, Samir Ranjan; Mahbub, Amina; Shahjamal, Mirja M; Kabir, Md. Mahbubul; Zafar, Tata (BRAC Research and Evaluation Division (RED), 2019)
How do some primary schools in Bangladesh succeed despite of well documented constrains they face? The major primary education research programmes conducted in Bangladesh over recent years have consistently demonstrated that the inputs to primary education are insufficient and often of poor quality, teaching and learning processes remain limited to a very narrow range of practice, and achievement levels are disappointingly low. Findings of the PSPMP study, Education Watch, ESTEEM classroom research and several official government documents and statistics reflect all the above. So how is it that certain schools manage to provide a high quality of education in the circumstances, when the problems exist for all? The survey-based methods commonly used to study the factors determining educational opportunity and outcomes have taken us some distance in understanding success and failure, but the complexity of the school as a living community demands that further insights be obtained by expanding the horizons of our research activities. To this end, the present study attempts to draw on anthropological and ethnographic research traditions to achieve original insights into what it feels like to live in and be part of a school, which really makes a difference. The quality of education has been defined in a broader sense, which includes strong community participation in school improvement, leadership quality of the school heads, teachers' active participation in mentoring the learners, healthy teaching learning atmosphere in the classrooms, putting students in the centre of educational setting, and learning achievement of the students. It has recognized that having all these characteristics in one school is too much to want - a school can be successful in any one or more of the above areas. Six case studies have prepared on purposively selected six successful primary schools in Bangladesh - five of these schools are government and one is registered non-government. These are located in six different districts viz., Bandarban, Chittagong, Dhaka, Jessore, Nawabganj and Pabna. Selection of the schools was guided by the Steering Committee fom1ed for the study. The Research and Evaluation Division of BRAC conducted the study.